Almond-shell biomass ash (ABA): A greener alternative to the use of commercial alkaline reagents in alkali-activated cement. (5th July 2021) - Soriano, Lourdes; Font, Alba; Tashima, Mauro M.; Monzó, José; Borrachero, Maria Victoria; Bonifácio, Thaís; Payá, Jordi
Highlights: Almond-shell biomass ash (ABA) was used as an activator in alkali-activated cement. Blast furnace slag (BFS) was mixed with ABA to prepare the binder. Potassium salts in ABA promoted the hydraulicity of BFS to produce C(K)-A-S-H gel. Better compressive strength for ABA/BFS was obtained compared to KOH-activated BFS. Very low CO2 emissions (50–60 kgCO2 eq/m 3 for ABA/BFS mortar) were calculated. Abstract: The use of almond-shell biomass ash (ABA) as an alternative component to the commercial reagents used in the activation of blast furnace slag (BFS) systems is investigated. The presence in its chemical composition of a high content of K2 O indicates that it can alkalinize the medium. 100% waste-based mixtures ABA/BFS were studied by micro- and macrostructural tests. A compressive strength of 44 MPa was achieved by the mortar with 25% ABA addition cured for 7 days at 65 °C. The microstructural analysis showed the formation of slightly different C(K)-A-S-H gels to those formed when using KOH. The use of ABA in BFS mortars is shown as a greener alternative for construction materials because the replacement of synthetic chemical reagents that produced around a 75–80% of reduction in the values of kgCO2 eq/m 3 material.